2019
DOI: 10.15666/aeer/1704_82358259
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Indoor Environmental Quality of Hospital Wards and Patients’ Outcomes: A Study of a General Hospital, Minna, Nigeria

Abstract: The objective of this study was to assess patients' perceptions of the indoor environment of wards in a hospital in terms of architectural design, thermal comfort, indoor air quality (IAQ), lighting and acoustical parameters. The study attempted to determine the factors influencing the perceived indoor environmental quality (PIEQ) and explored the relationships between the perceived importance of indoor environmental quality (PI-IEQ) and health recovery, health satisfaction and therapeutic ambience of the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Studies indicate these physical health systems that support disability sense of control as evidence-based health design, such as the availability of natural lightening, acoustic and ventilation (Attakora-Amaniampong et al ., 2022; Lifchez, 2022). Some authors believe that assessing room temperature, adjusting windows and controlling natural lighting are critical components of patients' sense of control (Ganesh et al ., 2021; Alfa and Öztürk, 2019). Empirical evidence in health studies indicated that the linkages between the physical health condition of hospitals and patients' health are extensive (Liu et al ., 2020; Fatima et al ., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies indicate these physical health systems that support disability sense of control as evidence-based health design, such as the availability of natural lightening, acoustic and ventilation (Attakora-Amaniampong et al ., 2022; Lifchez, 2022). Some authors believe that assessing room temperature, adjusting windows and controlling natural lighting are critical components of patients' sense of control (Ganesh et al ., 2021; Alfa and Öztürk, 2019). Empirical evidence in health studies indicated that the linkages between the physical health condition of hospitals and patients' health are extensive (Liu et al ., 2020; Fatima et al ., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A relaxing thermal setting enhances healing and preserves patients' wellness (Alfa & Öztürk, 2019). This is because if natural ventilation is inefficient, this will lead to an accumulation of internal heat gains from the huge number of residents and equipment in the wards and still air in most locations (Lan et al, 2017).…”
Section: 20 Literature Reviewmentioning
confidence: 99%
“…Wu et al [83] studied noise in the environment and how it affects the perception of comfort. Alfa and Öztürk [80] assessed patients' perceptions of the indoor environment in terms of architectural design, thermal comfort, indoor air quality (IAQ), lighting and acoustic parameters.…”
Section: Azmoon Et Al [58] Light Intensitymentioning
confidence: 99%